Polycarboxybetaine in advanced drug delivery systems: From structure-function relationship to therapeutic applications - Zhuang Liu; Yanan Zhai; Shunye Wang; Jiahui Bai; Dan Wang; Ziyang Wang; Xiang Gao; Jing Gao (International Journal of Pharmaceutics: X)
Zwitterionic polycarboxybetaines (PCBs), combining quaternary ammonium cations and carboxylate anions in their repeating units, have emerged as promising materials for drug delivery applications. Their exceptional hydration, biocompatibility, and antifouling properties make them attractive alternatives to polyethylene glycol (PEG), particularly given growing concerns about immunogenicity of PEG. PCBs can be functionalized through various methods, including modification of side-chain moieties, adjustment of spacer length between charged groups, and incorporation of responsive elements. When applied to delivery drug, PCBs have been successfully developed into multiple formats including micelles, hydrogels, liposomes, and nanoparticles. Notably, in protein drug delivery, PCBs demonstrate significant advantages such as enhancing protein stability, extending circulation time, improving penetration through biological barriers, and reducing immunogenicity. Despite these promising features, several challenges remain, including complex synthesis requirements, limited mechanical properties, and pending FDA approval as pharmaceutical excipients. This review provides a comprehensive analysis of PCBs from the structure-function relationship, synthesis methods, and applications in drug delivery systems, while examining current limitations and future prospects.